Identifikasi suhu permukaan terhadap penutupan lahan dari Landsat 8: studi kasus Kota Denpasar - Asmiwyati, I Gusti Agung Ayu Rai; Sugianthara, Anak Agung Gede; Wardi, I Nyoman (Jurnal Arsitektur Lansekap; Vol.6, No.2, Oktober 2020, 2020)
The variation of land surface temperature using Landsat 8, case study City of Denpasar. Land cover is an essential signature that is often used to understand interactions between local temperatures and land surfaces. The integration of remote sensing and geographical information system helps to effectively and efficiently extract data for a vast study area. The purpose of this study was to determine the range and distribution of Land Surface Temperature (LST) and the variation among land covers in City of Denpasar using Landsat 8. The City of Denpasar was selected as the representative study area where human population considerably increased high during past decade and thus, has posed a need to understand urban climates mainly for a city which located in a relatively small tropical island. This study shows that trees in mangrove, urban water areas, and paddy fields had lower LST and can be used as an effective means of offsetting the energy-intensive urban heat island effect.